1966
DOI: 10.1039/tf9666203559
|View full text |Cite
|
Sign up to set email alerts
|

Surface conductivity and conduction mechanisms on adsorption of vapours on silica

Abstract: Surface conductivity of a high surface-area porous silica adsorbent has been studied upon adsorption of CH3NO2, CsH6, dioxane, H20 and D20. For low surface coverages an exponential dependence between conductance and amount of gas adsorbed was found, whereas in the capillary condensation region the exponential dependence changed gradually to a linear one. The temperature dependence of the conductivity, appearance of polarization, and, with D20, the detection of electrolytic products proved that the conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…Moreover, the Anderson model forecasts an exponentially decreasing conductivity with increasing surface OH group concentration, whereas the opposite trend was found for the dehydroxilation of kaolinite earlier [135]. Conductivity was found to increase with the dipole moment of the adsorbed species in Vycor-glass [107]. Experimental proof for proton exchange between surface functional groups and adsorbed molecules was obtained in CH 3 OH/SiO 2 [136], water/SBA-15 [137] and various water/ sulphated polystyrene [138] systems.…”
Section: Dependence Of Charge Transport Processes On the Amount Of Admentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, the Anderson model forecasts an exponentially decreasing conductivity with increasing surface OH group concentration, whereas the opposite trend was found for the dehydroxilation of kaolinite earlier [135]. Conductivity was found to increase with the dipole moment of the adsorbed species in Vycor-glass [107]. Experimental proof for proton exchange between surface functional groups and adsorbed molecules was obtained in CH 3 OH/SiO 2 [136], water/SBA-15 [137] and various water/ sulphated polystyrene [138] systems.…”
Section: Dependence Of Charge Transport Processes On the Amount Of Admentioning
confidence: 77%
“…However, the qualitative [107] and quantitative [81] relationship between permittivity and conductivity was found by independent research groups even before this theory. These results indicate that conductivity increases due to the increase in permittivity during the adsorption process.…”
Section: Surface Conducting Mechanismsmentioning
confidence: 99%
“…Exposure to heavy water and demonstration of the presence of deuterium gas, like in Ref. 23, after stress and recovery of a transistor would provide definite proof.…”
Section: Summary Conclusion and Discussionmentioning
confidence: 99%
“…[23][24][25] It was shown that protons can be produced electrolytically from water on the SiO 2 surface by replacing water in the ambient by heavy water ͑D 2 O͒ and detecting deuterium gas ͑D 2 ͒ after performing surfaceconductivity measurements. 23 Therefore, we suggest that in the above experiments protons are responsible for the time evolution of the potential profiles. Because of the presence of silanol groups ͑SiOH͒ protons will be present on the SiO 2 surface because of the reaction SiOH SiO − +H + , creating an acidic environment.…”
Section: Proton Migration Mechanism For the Bias-stress Effectmentioning
confidence: 99%
“…It was shown long ago that protons can be produced electrolytically from water on the SiO 2 surface by the replacement of water in the ambient by heavy water ͑D 2 O͒ and the detection of deuterium gas ͑D 2 ͒ after performing surface-conductivity measurements. 18 Since organic semiconductors are permeable to water ͑and also to gasses like oxygen and hydrogen͒, water molecules can also reach the SiO 2 surface in the presence of a semiconducting layer. We propose that the production of protons now takes place throughout the accumulation layer in the semiconductor by electrolysis of water in the presence of holes, effectively converting holes into protons.…”
Section: Proton Migration Mechanism For the Instability Of Organic Fimentioning
confidence: 99%